2019
DOI: 10.1039/c9tx00186g
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic acid antagonizes paraquat-induced vascular endothelial dysfunction by suppressing mitochondrial reactive oxidative stress

Abstract: Paraquat (PQ) is a widely used herbicide in the agricultural field. The lack of an effective antidote is the significant cause of high mortality in PQ poisoning. Here, we investigate the antagonistic effects of alpha lipoic acid (α-LA), a naturally existing antioxidant, on PQ toxicity in human microvascular endothelial cells (HMEC-1). All the doses of 250, 500 and 1000 μM α-LA significantly inhibited 1000 μM PQ-induced cytotoxicity in HMEC-1 cells. α-LA pretreatment remarkably diminished the damage to cell mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It was also showed that ALA significantly induced endogenous antioxidants, upregulated ICAM-1 and vascular cell adhesion molecule-1 (VCAM-1), and inhibited metalloproteinaseand NF-kappa B (Shay et al, 2009). In addition, ALA revealed antioxidant capacity through suppressing oxidative stress induced human microvascular endothelial cells dysfunction (Pang et al, 2019;…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It was also showed that ALA significantly induced endogenous antioxidants, upregulated ICAM-1 and vascular cell adhesion molecule-1 (VCAM-1), and inhibited metalloproteinaseand NF-kappa B (Shay et al, 2009). In addition, ALA revealed antioxidant capacity through suppressing oxidative stress induced human microvascular endothelial cells dysfunction (Pang et al, 2019;…”
Section: Discussionmentioning
confidence: 94%
“…It was also showed that ALA significantly induced endogenous antioxidants, upregulated ICAM‐1 and vascular cell adhesion molecule‐1 (VCAM‐1), and inhibited metalloproteinase‐ and NF‐kappa B (Shay et al, 2009). In addition, ALA revealed antioxidant capacity through suppressing oxidative stress induced human microvascular endothelial cells dysfunction (Pang et al, 2019; Salari‐Moghaddam et al, 2019). Another potential mechanisms of action of ALA in improvement of endothelial dysfunction might be due its roles in enhancement of enzyme nitric oxide synthase and production of NO and improvement of mitochondrial mass and function (Zou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used as one of the dietary supplements to prevent and treat many diseases, including stroke, diabetes, neurodegenerative and hepatic disorders [13]. In experimental studies, ALA has shown bene cial effects against cardiovascular dysfunction [17], sepsis [18], endothelin dysfunction and oxidative stress [19], testicular dysfunction [20] and liver dysfunction [21]. Recently, ALA has been clinically tested for its bene cial effects in patients with bromyalgia pain [14], multiple sclerosis [22], obesity [23], β-thalassemia [24], diabetes [25], non-alcoholic fatty liver disease [26].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the effects of AEE on MAPK signaling pathways, including ASK1 and ERK signaling pathways, were investigated in an H 2 O 2 -induced oxidative stress model consisting of HUVECs and a paraquat (PQ)-induced oxidative stress model consisting of rats. It has been reported that PQ-induced toxicity in organisms is associated with the generation of free radicals and oxidative stress, causing severe injury to vascular, liver, lung and other tissues ( Zhao et al, 2017 ; Eftekhari et al, 2018; Pang et al, 2019 ). The PQ-induced rat oxidative stress model has been widely used in research on PQ poisoning and antioxidant drugs (Eftekhari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%